Statistical analysis plan for a cluster randomised controlled trial to compare screening, feedback and intervention for child anxiety problems to usual school practice: identifying Child Anxiety Through Schools-identification to intervention (iCATS-i2i) - Ball, Susan C.; Reardon, Tessa; Creswell, Cathy; Taylor, Lucy; Brown, Paul; Ford, Tamsin; Gray, Alastair; Hill, Claire; Jasper, Bec; Larkin, Michael; Macdonald, Ian; Morgan, Fran; et al. (Trials, 2024)
The Identifying Child Anxiety Through Schools-identification to intervention (iCATS-i2i) trial is being conducted to establish whether ‘screening and intervention’, consisting of usual school practice plus a pathway comprising screening, feedback and a brief parent-led online intervention (OSI: Online Support and Intervention for child anxiety), bring clinical and health economic benefits compared to usual school practice and assessment only — ‘usual school practice’, for children aged 8-9 years in the following: (1) the ‘target population’, who initially screen positive for anxiety problems according to a two-item parent-report child anxiety questionnaire — iCATS-2, and (2) the ‘total population’, comprising all children in participating classes. This article describes the detailed statistical analysis plan for the trial.